Cost-benefit analysis of the impact of initiatives taken by Suriname under the CSME 1996-98 : final report - Watson, Noel ([CARICOM Secretariat] [Georgetown]GY, 2000)
Sheds light on the issue of the net benefits to CARICOM Member States of initiatives implemented under the CARICOM Single Market and Economy as at the end of 1998. Concludes that very few initiatives had been implemented in Suriname as at the end of 1998. Outlines legal legislative as well as administrative changes that were put in place by Suriname to accommodate the move towards the CSME.